The Use of Ethylene Adsorbers in Tamarillo Stored With Active Modified Atmosphere Packaging - Joel Mika Silalahi; Elisa Julianti; Terip Karo-Karo (Universitas Sumatera Utara, 2014)
The study was conducted to determine the effect of ethylene absorbers and storage time in maintaining fruit quality of tamarillo. This research was conducted using a completely randomized design with 2 factor i.e type of ethylene adsorbers (P1,= KMnO4, P2 = Zeolites, P3= Activated Charcoal , and P4 = Without adsorbers ), and storage time ( L1= 5 days, L2 = 10 days, L3 = 15 days and L4 = 20 days). Parameters analysed were water content, weight lost, vitamin C content, total soluble solids, total acid, respiration rate, hardness, and color, organoleptic values ( color, smell, and texture ). The results showed that the type of ethylene adsorbers had highly significant effect on weight lost, vitamin C content, total soluble solids, total acid and fruit hardness had significant effect on oxygen concentration, and had the significant effect of water content, carbondioxide concentration, and organoleptic values color and aroma. Storage time had highly significant effect on weight loss, vitamin C content, respiration rate, organoleptic flavor and texture, significant affect the hardness, and had no effect on water content, total soluble solids and color. The treatment interaction had highly significant effect only on vitamin C content. KMnO4 could preserve the quality of tamarillo fruits up to 20 days of storage. Keywords : Active Modified Atmosphere Packaging, ethylene adsorbers, storage time,tamarilo,